Examining cannabis protective behavioral strategy use using multiple methods. Issue 4 (21st November 2019) - Prince, Mark A.; Jenzer, Tiffany; Brown, Whitney; Hetelekides, Eleftherios M.; Mumm, Rachel A.; Collins, R. Lorraine
Abstract : Purpose: Cannabis use among young adults is increasing, despite being associated with several negative consequences. Protective behavioral strategies (PBSs) are a potential mechanism of behavior change for reducing substance use, yet PBS use for cannabis is not well understood. The purpose of this paper is to further define and measure the PBS construct for cannabis. Design/methodology/approach: A community sample of cannabis users ( n =54) participated in eight focus groups discussing the use of PBSs. Participants completed surveys regarding demographics, cannabis use habits and cannabis problems. The authors also administered an existing measure of cannabis PBS and asked them to generate new or unique protective strategies that they had used or had heard of others using. Findings: Thematic analysis of qualitative focus group data provided information about cannabis users' reasons for regulating cannabis use (e.g. health or legal problems, interpersonal) as well as strategies to moderate cannabis use or attenuate their risk for experiencing adverse consequences (e.g. distraction, existential/spiritual strategies). Analyses of quantitative survey data revealed that use of PBSs was negatively correlated with cannabis outcomes. Perceived helpfulness of strategies was an important predictor of decreased cannabis use and adverse consequences. Research limitations/implications: Findings expand the understanding of the definition and measurement of strategies for regulating cannabis use and reducing related risk of experiencing adverse consequences. Originality/value: This is the first study to examine cannabis-related PBS using both qualitative and quantitative methods, which provide insights into the definition of PBS and for future refinements of PBS measurement.